2019
DOI: 10.1111/gbb.12613
|View full text |Cite
|
Sign up to set email alerts
|

A model of emotional stress‐induced binge eating in female mice with no history of food restriction

Abstract: Overeating is a major contributing factor to obesity and related health complications. For women, in particular, negative emotions such as stress strongly influence eating behavior and bingeing episodes. Modeling this type of binge eating in rodents presents challenges: firstly, stress‐induced anorexia is commonly observed in rodents therefore a mild stressor is required in order to observe an orexigenic effect. Second, many studies report using calorie restriction to observe the required behavior; yet this do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…BED is associated with a heightened response to stress (Anversa et al, 2020;Naish et al, 2019) and was one of the most commonly reported triggers of binge eating in our study. Despite only partial evidence for the association between BED and stress (Naish et al, 2019), in contrast to previous work, the stress in the current study was not experimentally induced.…”
Section: Perceived Stressmentioning
confidence: 55%
“…BED is associated with a heightened response to stress (Anversa et al, 2020;Naish et al, 2019) and was one of the most commonly reported triggers of binge eating in our study. Despite only partial evidence for the association between BED and stress (Naish et al, 2019), in contrast to previous work, the stress in the current study was not experimentally induced.…”
Section: Perceived Stressmentioning
confidence: 55%
“…Indeed, while a decrease or suppression of food intake in response to stress and negative mood has been conceived as the natural, typical, distress response because of physiological changes that mimic satiety [ 8 ], it is now acknowledged that important individual differences modulate the way people intake food in the same conditions, with as many as 30 to 50% of people who report eating more during stressful periods [ 9 ]. Consistently with seminal descriptions of the psychological aspects of hyperphagia and obesity made in the 1950s by Bruch [ 10 ], Hamburger [ 11 ], and Stunkard [ 12 ], and as conceptualized in the Emotionally Driven Eating Model [ 6 , 13 , 14 ], some individuals appear to be susceptible to unhealthy shifts towards energy-dense and highly palatable (HP) food items when being emotional [ 15 , 16 , 17 ]. Both experimental and epidemiological studies on this issue have consistently identified overweight and obese people as being particularly prone to these shifts, and these findings are part of the conceptual framework of the recently proposed Clinical Obesity Maintenance Model [ 6 ].…”
Section: Introductionmentioning
confidence: 71%
“…Potential effects of gonadal hormones on food intake have been used to justify the exclusion of females ( 57). Yet, studies that explicitly examined stress-induced feeding behaviors in female rodents across the estrous cycle do not support the idea that these fluctuations are a major source of variability (41,(58)(59)(60). However, there are some contexts when differences in the levels of gonadal hormones exert a strong effect on food intake, such as a severe fast (61) or adolescent stress (62).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%